Leafing patterns and leaf traits of four evergreen shrubs in the Patagonian Monte, Argentina - Campanella, María Victoria (2009)
We assessed leafing patterns (rate, timing, and duration of leafing) and leaf traits (leaf longevity, leaf mass per area and leaf-chemistry) in four co-occurring evergreen shrubs of the genus Larrea and Chuquiraga (each having two species) in the arid Patagonian Monte of Argentina. We asked whether species with leaves well-defended against water shortage (high LMA, leaf longevity, and lignin concentration, and low N concentration) have lower leaf production, duration of the leafing period, and inter-annual variation of leafing than species with the opposite traits. We observed two distinctive leafing patterns each related to one genus. Chuquiraga species produced new leaves concentrated in a massive short leafing event (5-48 days) while new leaves of Larrea species emerged gradually (128-258 days). Observed leafing patterns were consistent with simultaneous and successive leafing types previously described for woody plants. The peak of leaf production occurred earlier in Chuquiraga species (mid September) than in Larrea species (mid October-late November). Moreover, Chuquiraga species displayed leaves with the longest leaf lifespan, while leaves of Larrea species had the lowest LMA and the highest N and soluble phenolics concentrations. We also observed that only the leaf production of Larrea species increased in humid years. We concluded that co-occurring evergreen species in the Patagonian Monte displayed different leafing patterns, which were associated with some relevant leaf traits acting as plant defenses against water stress and herbivores. Differences in leafing patterns could provide evidence of ecological differentiation among coexisting species of the same life form.